2023
DOI: 10.1021/acsami.3c12735
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Strain-Sensitive Sensors Assembled from Mussel-inspired Hydrogel with Tunable Mechanical Properties and Wide Temperature Tolerance in Multiple Application Scenarios

Xiaoyong Zhang,
Shengyue Liang,
Fan Li
et al.

Abstract: Conductive hydrogels, exhibiting wide applications in electronic skins and soft wearable sensors, often require maturely regulating of the hydrogel mechanical properties to meet specific demands and work for a long-term or under extreme environment. However, in situ regulation of the mechanical properties of hydrogels is still a challenge, and regular conductive hydrogels will inevitably freeze at subzero temperature and easily dehydrate, which leads to a short service life. Herein, a novel adhesive hydrogel (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The two ends of the eutectogel were connected to copper wires, which were connected to a digital bridge to display the resistance change in real time. In the tensile sensing test, the sensitivity of the resistance response due to strain/stress of the eutectogel was calculated by the formula (GF): 32 GF = ( R − R 0 )/ R 0 ε R was the real-time test resistance value of the eutectogel, R 0 was the initial resistance value of the eutectogel, ε was the strain.…”
Section: Methodsmentioning
confidence: 99%
“…The two ends of the eutectogel were connected to copper wires, which were connected to a digital bridge to display the resistance change in real time. In the tensile sensing test, the sensitivity of the resistance response due to strain/stress of the eutectogel was calculated by the formula (GF): 32 GF = ( R − R 0 )/ R 0 ε R was the real-time test resistance value of the eutectogel, R 0 was the initial resistance value of the eutectogel, ε was the strain.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al proposed a self-adhesive hydrogel, and the adhesion mechanism is shown in Figure 8i. 192 PAA-Dopa gel can react with groups in the skin to form Michael-type or Schiff base reactions. Another strategy for preparing self-adhesive hydrogels is the synthesis of polyethylene glycol diacrylate (PEGDA), sulfobetaine methacrylate (SBMA) monomers, and Dopa.…”
Section: ■ Functional Characteristicsmentioning
confidence: 99%
“…(i) Schematic view of adhesion to the skin. Reproduced from ref . Copyright 2023 American Chemical Society.…”
Section: Functional Characteristicsmentioning
confidence: 99%
“…Among various soft polymers, flexible biomimetic conductive polymers are one of the most important i-skin candidates because they have biocompatibility, tunable conductivity, and certain flexibility, as well as the basic ability to convert biological signals (e.g., joint motions, facial microexpressions, and faint respiration) into easily detectable electrical signals. Of those materials, ionic hydrogels have shown great potential due to their physiological and mechanical properties that closely resemble those of biological tissues. Therefore, researchers are working on the development of various ionic hydrogel-based biomimetic materials to enable continuous, real-time, and noninvasive monitoring of personal health. For instance, Li et al., inspired by the tactile sensory mechanism of human skin, prepared a novel ionic hydrogel (PVA/PEG/TA-MXene-Na + /Li + , denoted as PPM-NL) enhanced by physically cross-linking, which showed good properties regarding mechanical strength (400% elongation at break, 0.93 MPa), ionic conductivity (8.1 S m –1 ), tear resistance, self-healing, and antifreezing/drying (frost resistance of −27 °C and 93% water retention after 60 days) .…”
Section: Introductionmentioning
confidence: 99%